A NiFe-Based Hierarchically Structured 3D Electrode by Hydrothermal Deposition for Highly Efficient Water Oxidation. (1st September 2017) - Tang, Weiqiang; Zuo, Shangshang; Wang, Jianying; Mi, Yongli; Chen, Zuofeng
Graphical abstract: Abstract: Herein, nanostructured FeOOH supported on the 3D nickel foam (FeOOH-NF) was prepared by a facile one-pot hydrothermal deposition. A series of analytical techniques indicate formation of a layered uniform nanosheets from the underlying nickel foam which incorporate in situ generated FeOOH. Thanks to the synergistic interaction between Fe and Ni and the good electrical connection between the active catalyst and conductive substrate by the direct growth, the hierarchically structured electrode exhibits high electrocatalytic performance for the oxygen evolution reaction (OER) in alkaline solution with low overpotential, small Tafel slope and excellent long-term durability. In 1 M KOH, a current density of 20 mA/cm 2 is achieved at an overpotential of only 210 mV with a Tafel slope of 29 mV/decade, which is competitive or superior to various electrocatalysts on the 3D nickel foam under similar conditions. Considering the simple and facile electrode preparation, the low cost and environmental friendliness of the electrode materials, and the excellent catalytic performance, the FeOOH-NF electrode would be a promising anode candidate for the OER in large scale water electrolysis.